Peranan Peserta KKN Tematik Dalam Meningkatkan Kepatuhan Penggunaan Masker Pada Masa Pendemi Covid-19 di Kota Kendari - Adryan Fristiohady (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The use of this mask has an important role in anticipating Covid-19 virus. If the community has knowledge about the use of masks, the community will also be obedient in the use of masks. Compliance is to describe the positive behavior of the people shown by using. Through this Thematic Community Service Program, the community can know the benefits of using masks in preventing Covid-19. the method used in the integrated community service activities of Thematic KKN is the method of socialization, the method for the environment of student residence, the method of media networking and reporting methods.Thematic KKN takes place in the city of Kendari, Sulawesi Tenggara